HRES-1/Rab4 promotes the formation of LC3(+) autophagosomes and the accumulation of mitochondria during autophagy. - Gergely Talaber; Gabriella Miklossy; Zachary Oaks; Yuxin Liu; Sharon A Tooze; Dmitriy M Chudakov; Katalin Banki; Andras Perl (PLoS ONE)
HRES-1/Rab4 is a small GTPase that regulates endocytic recycling. It has been colocalized to mitochondria and the mechanistic target of rapamycin (mTOR), a suppressor of autophagy. Since the autophagosomal membrane component microtubule-associated protein light chain 3 (LC3) is derived from mitochondria, we investigated the impact of HRES-1/Rab4 on the formation of LC3(+) autophagosomes, their colocalization with HRES-1/Rab4 and mitochondria, and the retention of mitochondria during autophagy induced by starvation and rapamycin. HRES-1/Rab4 exhibited minimal baseline colocalization with LC3, which was enhanced 22-fold upon starvation or 6-fold upon rapamycin treatment. Colocalization of HRES-1/Rab4 with mitochondria was increased >2-fold by starvation or rapamycin. HRES-1/Rab4 overexpression promoted the colocalization of mitochondria with LC3 upon starvation or rapamycin treatment. A dominant-negative mutant, HRES-1/Rab4(S27N) had reduced colocalization with LC3 and mitochondria upon starvation but not rapamycin treatment. A constitutively active mutant, HRES-1/Rab4(Q72L) showed diminished colocalization with LC3 but promoted the partitioning of mitochondria with LC3 upon starvation or rapamycin treatment. Phosphorylation-resistant mutant HRES-1/Rab4(S204Q) showed diminished colocalization with LC3 but increased partitioning to mitochondria. A newly discovered C-terminally truncated native isoform, HRES-1/Rab4(1-121), showed enhanced localization to LC3 and mitochondria without starvation or rapamycin treatment. HRES-1/Rab4(1-121) increased the formation of LC3(+) autophagosomes in resting cells, while other isoforms promoted autophagosome formation upon starvation. HRES-1/Rab4, HRES-1/Rab4(1-121), HRES-1/Rab4(Q72L) and HRES-1/Rab4(S204Q) promoted the accumulation of mitochondria during starvation. The specificity of HRES-1/Rab4-mediated mitochondrial accumulation is indicated by its abrogation by dominant-negative HRES-1/Rab4(S27N) mutation. The formation of interconnected mitochondrial tubular networks was markedly enhanced by HRES-1/Rab4(Q72L) upon starvation, which may contribute to the retention of mitochondria during autophagy. The present study thus indicates that HRES-1/Rab4 regulates autophagy through promoting the formation of LC3(+) autophagosomes and the preservation of mitochondria.